2016
DOI: 10.18632/oncotarget.14128
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 confers promotion in gastric cancer through modulating downstream CRKL in vitro combining with biostatistics mining

Abstract: ABCG2, member of ATP-binding cassette (ABC) transporter family, is known as crucial regulator related to multi-drug resistance in human tumors and has recently been putatively studied as human carcinoma cell biomarker. While, effects of ABCG2 on human gastric cancer (GC) has not been illustrated thoroughly. In this study, by applying biostatistics mining methods, we observed that ABCG2 is frequently aberrantly expressed in GC patients through exploring dataset of GSE19826 in NCBI GEO database. Contemporary, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Therefore, the assessment of differential expressions of BRCP may lead the scientific community to create a new method to evaluate progression, metastasis and to predict therapeutic response of colorectal cancer. The results also corroborate with the findings of Wang and colleagues, who, through an in vitro experiment, demonstrated that the ABCG2 gene shows dysregulated expression in GC tissues and cells [28]. In this study, the high expression of ABCG2/BRCP was correlated with advanced stages and poor prognosis of GC.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the assessment of differential expressions of BRCP may lead the scientific community to create a new method to evaluate progression, metastasis and to predict therapeutic response of colorectal cancer. The results also corroborate with the findings of Wang and colleagues, who, through an in vitro experiment, demonstrated that the ABCG2 gene shows dysregulated expression in GC tissues and cells [28]. In this study, the high expression of ABCG2/BRCP was correlated with advanced stages and poor prognosis of GC.…”
Section: Discussionsupporting
confidence: 92%
“…The cell proliferation curves were plotted. Methods above refer to our previous research 19 . The aforementioned cells were treated in steps with ethanol fixation, RNase A treatment and propidium iodide staining.…”
Section: Methodsmentioning
confidence: 99%
“…It has been revealed that MRP1-3 lead to resistance to hydrophobic and anionic compounds, including several natural compounds, whereas MRP4, MRP5 and MRP8 efflux cyclic nucleotides (13,14). BCRP, a ubiquitous ABC transporter, has been shown to transport nucleoside drugs and nucleoside-monophosphate derivatives of clinically relevant nucleoside drugs (15,16). Moreover, these ABC transporters are highly expressed in various human cancer types and are closely associated with poor prognosis (17,18).…”
Section: Effect Of Sodium Butyrate On Abc Transporters In Lung Cancermentioning
confidence: 99%